2018
DOI: 10.1016/j.renene.2017.11.035
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to estimating temperature fields around a group of vertical ground heat exchangers in two-dimensional analyses

Abstract: Vertical ground heat exchangers (VHEs), in the form of either Borehole Heat Exchanger (BHE) or thermo-active piles, are increasingly being deployed to provide low cost and sustainable heating and cooling to buildings. These are often installed within densely built urban environments, where adjacent foundation systems and underground structures can be affected by soil temperature changes induced by the heat exchangers. Therefore, they need to be considered in the geotechnical design of such structures, which ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…One year of operation was simulated, with balanced heat extraction and injection, each over a period of six months. An appropriate equivalent heat load to account for the two-dimensional nature of the analyses was applied and results with the correction factor * proposed by [16] are compared to those obtained with the conventional approach whereby the heat flux is simply divided by the out-of-plane spacing between VHEs. The use of the correction factor * was deemed fundamental in the performed analyses since [16] showed that its use leads to a more accurate estimate of the temperature field in 2D plane strain analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One year of operation was simulated, with balanced heat extraction and injection, each over a period of six months. An appropriate equivalent heat load to account for the two-dimensional nature of the analyses was applied and results with the correction factor * proposed by [16] are compared to those obtained with the conventional approach whereby the heat flux is simply divided by the out-of-plane spacing between VHEs. The use of the correction factor * was deemed fundamental in the performed analyses since [16] showed that its use leads to a more accurate estimate of the temperature field in 2D plane strain analyses.…”
Section: Resultsmentioning
confidence: 99%
“…[15]). Due to the twodimensional (2D) nature of the analysis, an equivalent heat flux, 2 , was applied following the procedure outlined by [16]:…”
Section: Vertical Heat Exchangersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, out of plane effects due to heat transfer, mass transfer and deformation phenomena are not considered. Although such approximation may be regarded as noteworthy [127], mathematical formulations allowing to correct the results of these numerical investigations have been presented for both energy piles [128] and energy walls [129].…”
Section: Reduction Of Problem Dimensionsmentioning
confidence: 99%
“…Therefore, it is advantageous to calculate the lower parameters of the heat source as accurately as possible. There are many attempts to solve this problem in an analytical way and with the help of computer simulations [12][13][14][15][16][17][18][19][20][21][22][23][24], but so far there is no universal formula. Real measurement results are required for calculations and simulations.…”
Section: Introductionmentioning
confidence: 99%